Implementasi Pembiayaan Salam dan Qardhul Hasan pada Usaha Pertanian Indonesia - Aftina Nurul Khusna; Puji Lestari (JIOSE: Journal of Indonesian Sharia Economics, 2022)
Indonesia is known as an agricultural country because most of the population works as farmers. The agricultural sector is one of the government's priority agendas out of nine existing agendas, namely realizing economic independence by moving strategic sectors of the domestic economy. However, in its operations, the agricultural sector has various problems, one of which is the problem of different economic conditions and constraints on farmers which results in Indonesia's agricultural potential being underutilized to its full potential. The diversity of financing at Islamic financial institutions can be utilized by farmers or other related parties by using financing that is in accordance with the level of the community's economic condition and the type of use, so that the financing can be targeted and improve the welfare of farmers. This research is a type of descriptive qualitative research that aims to describe the implementation of salam and qardhul hasan financing in an effort to improve the economy of farmers and explore the potential of Indonesian agriculture, as well as how the challenges of implementing this financing for Islamic financial institutions are. This research is based on qualitative research with descriptive analysis methods from various literatures. The results obtained from this study indicate that the implementation of salam and qardhul hasan financing has a positive impact on farmers, namely it can increase farmers' capital so that they can develop their agriculture and improve economic welfare.